Changes on Sugar and Starch Contents during Seed Development of Synergistic Sweet Corn and Implication on Seed Quality - Bhornchai Harakotr; Warisa Sutthiluk; Panumart Rithichai (International Journal of Agronomy)
Synergistic sweet corn equipped with multiple-recessive genes encoding sugar synthesis is proposed through hybrid breeding to improve the balance eating quality including flavor, texture, and aroma. However, the drawback on seed quality occurs such as low germination and poor seedling vigor. This study aimed to investigate the changes of carbohydrate contents on seed quality of five sweet corn genotypes differing in the number of equipped recessive genes during seed development. Seeds were sampled at 4-day intervals from 18 to 46 days after pollination (DAP) and analyzed for seed germination, sugar, water-soluble polysaccharide, and starch. Then, their relationships were analyzed by using time series regression analysis. Although there were significant differences among 5 corn genotypes in their seed germination and carbohydrate contents, some genotypes showed responses in similar patterns. The optimal time to harvest seeds was genotype-dependent, which were 38 DAP for triple-recessive gene (btbtsh2sh2wxwx) and single-recessive genes (BtBtsh2sh2WxWx and Sh2Sh2susuWxWx) and 42 DAP for double-recessive genes (BtBtsh2sh2wxwx). The regression analysis revealed that seed germinability could be predicted by total starch content in synergistic sweet corn lines during seed development stages; however, this prediction seemed to be negligible in sweet corn genotypes equipped with a single-recessive gene. Implications and further suggestions for establishing an effective seed production technique and seed quality of synergistic sweet corn are discussed.